Faktor-Faktor yang Mempengaruhi Kejadian Stunting terhadap Balita menggunakan Analisis Regresi Logistik - Safitri, Elfira; Basriati, Sri; Mulyani, Septia (Zeta - Math Journal, 2022)
Stunting is a condition of failure to thrive in toddlers due to chronic malnutrition, resulting in toddlers or children being too short for their age standards. The purpose of the study was to determine the factors that influence the incidence of stunting to toddlers at the Public Health Center Kasih Ibu airtiris, kampar. The method used in this study is the binary logistic regression method. Based on the results of the study indicate that the factors that influence the incidence of stunting in toddlers at Public Health Center Kasih Ibu airtiris, kampar namely the nutritional status of body weight based on age. The binary logistic equation with the resulting logit function is . The value of the determination of the classification of stunting events using binary logistic regression is 83,6%.